POTENTIAL EVALUATION OF SOME CROSSES AS RESTORER PARENT ON HYBRID RICE DEVELOPMENT - Yuniati Pieter Munarso (Pusbindiklat - LIPI, 2011)
Development of hybrid rice using three-lines method in Indonesia is handicapped by low and varied restor-ing ability of restorer line. Most of available restorer line showed to have varied fertility in its F1 resulted from test cross. This experiment was executed to evaluate some crosses resulted anther culture seed and cytoplasmic male sterile as potential restorers. Amount of 32 crosses were planted and grew in rice fi eld. Observations were made on spikelet fertility, 50% fl owering age, anther color, and phenotypic acceptability. Result shows that 4 (four) crosses were found to have spikelet fertility of more than 75%. They were IR70731A/KA74-2, IR70364A/KA78-2, IR58025A/KA26-2, and IR70731A/KA15-2. This result indicated that the male parent of those crosses could be concluded as potential restorer lines